Orissa's economic development : experiences and expectations - Panda, Raj Kishore; Panda, Raj Kishore (Serials Publ., 2009)
Papers presented at the National Workshop on Orissa's Economic Development : Experiences and Expectations, held at Bhubaneswar during 29-30 August 2008